Protective effects of geraniol in a male rat model of Alzheimer's disease: A behavioral, biochemical, and histological study - Bagheri, Shokufeh; Rashno, Masome; Salehi, Iraj; Karimi, Seyed Asaad; Raoufi, Safoura; Komaki, Alireza (Journal of Alzheimer's disease, 2024)
Alzheimer's disease (AD) as a neurodegenerative disease can cause behavioral impairments due to oxidative stress. Aging and oxidative conditions are some AD risk factors. We assessed the influence of geraniol (GR), an acyclic monoterpene alcohol, on behavioral functions, hippocampal oxidative status, and histological alterations in AD rats induced by amyloid-β (Aβ). Male Wistar rats (n = 70) were randomly allocated to the control, sham, AD, control-GR (100 mg/kg; per oral: P.O.), AD-GR (100 mg/kg; P.O.; treatment), GR-AD (100 mg/kg; P.O.; pretreatment), and GR-AD-GR (100 mg/kg; P.O.; pretreatment + treatment) groups. GR administration was done for four continuous weeks. After treatments, novel object recognition (NOR) and Morris water maze (MWM) tests assessed the animals' behavior. Then, hippocampal specimens were collected for biochemical assessment. Finally, the number of intact neurons was identified in the hippocampus using hematoxylin and eosin staining. Aβ microinjection increased learning and memory deficits in both NOR and MWM tests, oxidative stress status, and neuronal loss. Oral GR administration improved behavioral deficits and reduced oxidative stress status and neuronal loss in the Aβ-infused animals. GR ameliorates behavioral impairments through a decrease in neuronal degeneration and oxidative stress.